Development of Prototype Pico Hydropower Generation - Mohamad, Muhammad Fakhrul Aizat; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2022)
In Malaysia, various types of renewable energy are used to produce clean and green energy. One renewable energy is hydroelectric energy uses water resources to produce electricity. Various types of hydropower according to the amount of energy produced range from large energy which is more than 100MW to pico energy which is less than 50kW. In this paper, the project has been tested on a small agricultural area where the place is rarely used and the small area is suitable for producing small and portable energy. For this project, the Pico hydropower is generated by using a Pelton turbine as mechanical energy and a generator as electrical energy which have been combined into one generator. It is connected to a water flow sensor which will read the speed of water flowing through the pipe and also the volume of water. By the Arduino Uno, the system can measure the water flow rate, the volume of water and the voltage output. This system is tested by generating the speed of water flow according to time which is proportional to 2 minutes per reading. Starting with the first 2 minutes, the water velocity rate is 12.04L/min with a water volume of 22.0L and 20 minutes later, the total water flow rate is 115.32L/min with a nearly equal water volume of 22.53L. The voltage output at the full opening of the water level is 11.67V and the partial opening is 6.98V. The energy generated is used on an LED lamp that uses 5V, 5W. Finally, it is found that a pico hydropower prototype can be built and generate electricity using the generator and turbine with pressurized water to use at DC loads.